Use and application of range mapping in assessing extinction risk in Canada - Craig Loehle; Darren J. H. Sleep (Wildlife Society Bulletin, 2015)
ABSTRACT When a species potentially at risk of extinction is considered for legally protected status, changes in geographic range over time are often evaluated and utilized in listing decisions. Range changes are also used to guide conservation management decisions. Although changes in geographic range may provide information relevant to conservation decisions, many factors affect estimates of geographic range. We investigated how geographic range change is estimated and used in the listing process. We evaluated all terrestrial vertebrates in Canada whose assessment as threatened or endangered was based at least partially on small range or range reduction. The 39 cases of birds, mammals, reptiles, and amphibians (including 2 populations of 1 species) used a variety of historical and recent data, including natural history archives, special surveys, and standardized surveys. Little mention was made in the reports of the methods used for range delineation or the limitations of geographic range maps. Of the 39 cases listed by the reports as being threatened or endangered in Canada at least in part due to geographic range, 32 (82%) had ≤10% of their current global range in Canada (i.e., most had wide ranges in the United States), resulting in the listing of species with marginal and sometimes nonviable populations within Canada even when the global population was not at risk. We identify several ways that listing decisions could be improved. © 2015 The Wildlife Society.